(untitled) (Biodiversitas Journal of Biological Diversity, 2009)
The aim of this survey was to know the abundance status of the Yellow-crested Small Cockatoo (Cacatua sulphurea parvula) and Yellow-headed Lorikeet (Trichoglossus euteles) in Alor, East Nusa Tenggara Province. There were four observation sites in the survey, namely: (i) Air Mancur preparatory Village (in and around of Tuti Adigae Natural Tourism Park, East Alor Sub-district), (ii) Tanglapui Village (Kampong Irawuri) (East Alor Sub-district), (iii) Probur Village (Kampong Wormanem) (Southwest Alor Sub-district), and (iv) Bota Village (Northwest Alor Sub-district). The survey was used for the bird encounter rates per unit time method. The bird population was estimated by abundance score value. Fifty species of birds or 64.9% of 77 species of birds occurring in Alor were recorded during field work. The yellow-headed lorikeet observed was more abundant with five abundance score and for the numbers per 10 hours observation were 58.06. There was no yellow-crested small cockatoo observed during the survey. However, the yellow-crested small cockatoo was presumed to be present in the fields by the direct observation of old nest site of Canarium trees. Key words: parrot, population, Cacatua sulphurea parvula, Trichoglossus euteles, Alor